Light-intensity and thickness dependent efficiency of planar perovskite solar cells: charge recombination versus extraction. Issue 36 (27th August 2020) - Du, Tian; Xu, Weidong; Xu, Shengda; Ratnasingham, Sinclair R.; Lin, Chieh-Ting; Kim, Jinhyun; Briscoe, Joe; McLachlan, Martyn A.; Durrant, James R.
Abstract : We reveal the complex interplay between photoactive layer thickness and illumination intensity in perovskite solar cells, presenting design criteria for real-world and solar concentrator applications. Abstract : Photoactive layer thickness is a key parameter for optimization of photovoltaic power conversion efficiency (PCE), yet its impact on charge extraction and recombination hasn't been fully understood in perovskite solar cells (PSCs). Herein we find that in planar PSCs the perovskite thickness yielding maximal PCE is strongly light-intensity dependent. Whilst under 1 sun irradiation the PCE is relatively invariant for perovskite thicknesses between 250 to 750 nm, at lower light intensities (0.1–0.5 sun) the thickest devices yield strongly enhanced PCE, but at higher light intensities (>1 sun) the thinnest devices give optimal PCE. Our results unravel that increased perovskite thickness leads to enhanced light absorption, reduced interfacial recombination at open circuit but greater bimolecular recombination losses at short circuit thus is suitable for devices working under weak illumination, typical of many real-world applications. Reducing perovskite thickness, however, shows the contrast trend and is suitable for PSCs working under concentrated illumination.